Design of Shape Memory Alloy-Based and Tendon-Driven Actuated Fingers Towards a Hybrid Anthropomorphic Prosthetic Hand - KAPLANOĞLU, ERKAN (SAGE PUBLICATIONS INC, 2012)
This paper presents the design of tendon-driven actuated fingers using a shape memory alloy for a hybrid anthropomorphic prosthetic hand. The ring and little (pinky) fingers are selected for shape memory activation due to their lower degree of movement during multiple grasping configurations. The fingers' tendon system is based on shape memory alloy (SMA) wires that form artificial muscle pairs for the required flexion/extension of the finger joints. The finger has four degrees of freedom such that three of them are active. An experimental setup was developed to evaluate the performance of the ring and little fingers. An electromyography (EMG) controlled Pulse Width Modulated (PWM) technique is preferred for the actuation of joint motions using a high speed microcontroller.
Keywords: Anthropomorphic prosthetic hand; Shape memory alloy